Strategies for Speed Breeding in Crops to Accelerate Plant Improvement - Naglaa A, Abdallah; Hamwieh, Aladdin; Radwan, Khaled; Baum, Michael (CRC Press, 2024)
Plant breeding aims to create new varieties with enhanced yield and quality. Speed breeding has emerged as a particularly potent strategy, effectively reducing crop generation time and accelerating breeding programs for crop improvement. This innovative approach encompasses a set of advanced methods intended to expedite agricultural enhancement by promoting faster plant growth and development. It can take several years to create new crop varieties with desirable characteristics using traditional breeding techniques, which are frequently slow. However, with the use of speed breeding strategies, crops can be developed in a matter of months rather than years. An overview of the most popular speed breeding techniques, including tissue culture and doubled haploid, genetics, long-period light exposure techniques, and agriculture in controlled environments, is given in this chapter. These strategies can be used individually or in combination with new breeding technologies such as genome editing to achieve even faster results. Reports have highlighted the implementation of speed breeding techniques in crops like wheat, rice, barley, and maize. The substantial advantages of speed breeding in enhancing food security and building resilience against climate change are noteworthy. Nevertheless, it is important to acknowledge any potential risks or concerns associated with these techniques, including potential environmental impacts and the need for rigorous safety assessments. In general, incorporating speed breeding into crop enhancement initiatives can lead to faster development of new crop varieties with improved traits, ultimately helping to address global food security challenges.